Anti-emetic mechanisms of zingiber officinale against cisplatin induced emesis in the pigeon; behavioral and neurochemical correlates - Ullah, Ihsan (BMC Complement Altern Med, 2015)
BACKGROUND: Zingiber officinale (ZO, family Zingiberaceae) has been reported for its antiemetic activity against cancer chemotherapy induced emesis in animal models and in clinics. Current study was designed to investigate ZO for potential usefulness against cisplatin induced vomiting in pigeon and its effects on central and peripheral neurotransmitters involved in the act of vomiting. METHODS: Zingiber officinale acetone fraction (ZO-ActFr) was investigated for attenuation of emesis induced by cisplatin in healthy pigeons. Neurotransmitters DA, 5HT and their metabolites DOPAC, HVA and 5HIAA were analyzed using High Performance Liquid Chromatography system coupled with electrochemical detector in area postrema, brain stem and intestine. Antiemetic effect of ZO-ActFr was correlated with central and intestinal neurotransmitters levels in pigeon. RESULTS: Cisplatin (7 mg/kg i.v.) induced emesis without lethality upto the observation period. ZO-ActFr (25, 50 & 100 mg/kg) attenuated cisplatin induced emesis ~ 44.18%, 58.13% (P < 0.05) and 27.9%, respectively; the reference drug, metoclopramide (MCP; 30 mg/kg), produced ~ 48.83% reduction (P < 0.05). ZO-ActFr reduced (P < 0.05 - 0.001) 5-hydroxytryptamine (5HT) concentration in the area postrema, brain stem and intestine at 3(rd) hour of cisplatin administration, while at the 18(th) hour ZO treatments attenuated the dopamine upsurge (P < 0.001) caused by cisplatin in the area postrema and 5HT concentration (P < 0.01 - 0.001) in the brain stem and intestine. ZO treatments alone did not altered the basal neurotransmitters and their metabolites in the brain areas and intestine. CONCLUSION: The behavioral study verify the antiemetic profile of ZO against cisplatin induced emesis in the pigeon, where central and peripheral neural evidences advocate the involvement of serotonergic mechanism at initial time point (3(rd) hr), while the later time point (18(th) hr) is associated with serotonergic and dopaminergic component in the mediation of its antiemetic effect.